Особливості функціонування та регулювання ринку праці та соціальної політики в сучасній Польщі: досвід для України - Карлін, М.І. (Інститут демографії та соціальних досліджень НАН України, 2008)
В статье анализируются особенности современного рынка труда в Польше, изменения, которые состоялись на нем после вступления Польши в Европейский Союз, причины массового выезда поляков на работу за границу, официальная и реальная безработица в стране, проблемы финансирования социальной помощи для безработных и возможные пути их решения, которые можно применять и в Украине. The article deals with the distinguishing features of nowadays labour market in Poland, changes happened after the Poland’s entrance into the EU, reasons of great emigration of Polish workers in abroad, official and real unemployment in the country, problems connected with the financing of the social allowance in case of unemployment and possible ways of their solving and their application in Ukraine.